On Quantification of Incidence and Intensity of Poverty: A Global to Local Preview - Dutta, Durba; Khataniar, Rabinjyoti (Archives of Business Research, 2022)
The study aims to explore and quantify poverty from global to local context based on available secondary data published by the World Bank and Planning Commission of India. The study reveals that the global absolute number of poor and poverty ratio has declined in spite of the increase in total global population. At the National level, not only the poverty ratio but also the poverty gap has declined. However, the disparity in the number of poor people in its complete term points out a different trend of poverty, i.e., poverty in India was getting tilted to urban poverty. Almost all developing economies have been showing the same trend; a large proportion of the urban poor live on less than 1 a day. The incidence of poverty in the state of Assam has been on a declining trend since 1973-74. However, Assam has experienced an increase in absolute poverty, both rural and urban, as a result of the state's rapid population growth and others. The study recommended institutional initiatives for continuous monitoring of official poverty data, which has been suspended since 2011. It is also essential to have a new poverty assessment based on multidimensional components like access to health care, education, sanitation, and living spaces with social distance along with income.